Penerapan Metode Weighted Product (WP) Berbasis Sistem Pengambilan Keputusan Untuk Pemberian Dana Bantuan Mandiridesa Wisata Pada Dinas Perhubungan Pariwisata Kabupaten Bone Bolango - Irfan Abbas (Universitas PGRI Semarang, 2016)
Abstract - The Ministry of Tourism and Creative Economy implemented PNPM Mandiri Tourism Sector which entered the fifth year to support Tourism development activities through Community Empowerment in the tourist village. The support Decisioned by Tourism Transport Agency was not effective to set Desa Wisata which possibel to receive the PNPM support program. Its affects to the tourism business improvement of districts bone Bolango which inhibited. The support for society Desa Wisata through PNPM Mandiri program, Must meet the criteria. Such Potential criteria lay Desa Wisata must have the uniqueness and appeal of Tourism (as a tourist attraction), either form character of physical environment rural nature and socio-cultural Community, have support and readiness have been worn supporting for tourism. For a review of the support the matter as above will designed a decision support system using method weihgted product Interest to boost business tourism in the district Bone Bolango because supported by the best result of decision support. Keywords:Decision Support Systems, Weighted Product